STUDI PERBANDINGAN EFISIENSI ENERGI DAN BIAYA OPERASIONAL KOMPOR INDUKSI DAN LPG BERBASIS IOT - A. Andriani; H.C Soetanto; G.K. Sandy; I. N. S. Kumara; W. G. Ariastina (Jurnal SPEKTRUM, 2025)
This study designs an Internet of Things (IoT)-based monitoring system for 2 kW induction and 2 kW LPG stoves, supporting Indonesia's 2060 Net Zero Emission energy transition policy. Utilizing Arduino Mega 2560 with ESP8266, PZEM-004T sensor, K-type thermocouple, load cell, and Blynk platform, the system provides real-time monitoring of voltage, current, power, temperature, gas mass, and operating time. Data is accessible via a mobile application and stored on an SD card for analysis. Safety features include remote electricity/gas cut-off and active stove notifications. Testing reveals the induction stove's higher efficiency, heating 400 ml of cooking oil in 193 seconds with 0.06 kWh, compared to the LPG stove's 281 seconds with 19.18 grams of gas. Operational cost analysis indicates the induction stove is more economical (Rp 101.97) than subsidized LPG (Rp 159.87), suggesting a more favorable long-term investment for induction technology. By facilitating data collection, remote control, and review, the proposed system allows for evaluation of both technical and economic efficiencies. This study offers an IoT based technical solution and economic assessment that support the national policy shift toward induction stove.